Fatigue S-N curves of bolts and bolted connections for application in civil engineering structures. (October 2021) - Maljaars, Johan; Euler, Mathias
Highlights: A meta study into fatigue of bolts and bolted connections. Most details benefit from sub-grouping in FAT classes based on production process. There is a need for more fatigue tests at high stress ratios. Net section stress is not suited for evaluation of non-preloaded bolted connections. The article forms the background of the revision of the European standard EN 1993-1-9. Abstract: Bolts and bolted connections are frequently used in civil engineering steel structures. This paper presents a meta study where a few thousand fatigue tests on these elements are evaluated. The evaluation reveals that current specifications in design standards need updating to account for the relevant stress parameter and production methods. This substantially reduces the scatter of the fatigue resistance. The shape and position of the fatigue resistance (S-N) curves also require updating. The results of this study have been implemented in the new revision of European standard EN 1993-1-9. This paper provides the background for the modifications.